Types of collective farms in Poland - Galeski, Boguslaw (Wisconsin : Land Tenure Centre, University of Wisconsin-Madison, 1972)
Poland's collective farms are generally classified according to the statutes they follow. There were three model statutes from which farmers forming cooperatives could choose. Type 1 maintained individual control of the means of production; type 2, the entire farm was cultivated in common and; type 3 differed from the preceding in that income was distributed only according to the input of labour.
ne 12/08/2021
Loans
Keywords: Collective farms; Poland